STATE AND NEEDS OF THE EDUCATIONAL MANAGEMENT OF MOSQUE-BASED ISLAMIC EDUCATIONAL CENTERS (TADIKA) IN THREE SOUTHERN BORDER PROVINCES - Mitranun, Chanida; Prasertsin, Ujsara; Loppraserta, Anchleeporn (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
ABSTRACT The research surveyed state and needs of educational management of TADIKA in the three SouthernBorder Provinces. The participants consisted of five administrators, nine teachers, five parents, nine alumni, onemember of an Islamic committee, and eight member of TADIKA group in the three Thai southern border provinces.The data were collected through documents, observation, interview, and focus group. The data were analysedthrough the content analysis. The results of the research revealed that the educational management consisted offive areas which were curricula, personnel, budget, general administration, and community members’ participation.The findings regarding state and needs of stakeholders of TADIKA in three southern border provinces would beused as guidelines of educational management in line with and respond to the needs of the local and focus onthe participation of partners in every sector to achieve a systematic and sustainable development. Keyword : State and needs, Mosque-based Islamic educational centres, TADIKA, Southern Border Provinces